Life Balance in the Tafsir of Al-Misbah and Ibn Kathir - Afifatun Nisa Hasibuan; Arifinsyah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research explores the concept of balanced living (